Inclusive Climate Governance: Ensuring Women’s Voices Shape India’s Low-Carbon Transition - Chowdhuri, Jaydeb Ghosh; Chowdhury, Sudeshna (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
Existing gender inequalities are likely to worsen with climate change and the importance of ensuring inclusive climate governance cannot be overemphasised. This article explores how playing the gender-responsive card can help drive stronger low-carbon transition in India on the understanding that women (particularly in rural and poor areas) suffer/disproportionately bear higher brunt of climate impacts and yet have critical knowledge for sustainable solutions. We employ feminist political ecology, participatory governance, and intersectional feminist methodology to analyse gender relations and climate policy making. A heady glass raised and quaffed to mother earth and a partial review of literature and history — from the parts of environment where women have advanced conservation in significant ways, like the Chipko movement, to recent research — on how critical it is that women be part of environmental conservation; a litany about how policy framework after policy framework keeps failing to move women’s voices from margin to centre. Using empirically derived examples of women’s grassroots action as bare minimum women have been enrolled, results of climate adaption interventions increase whether it is community forestry programmes, ‘climate-smart’ agriculture initiatives or disaster risk preparedness. Through this analysis, focusing on climate policies and disaster management in place in India now, we highlight gaps that continue to undermine effective action on climate and disaster, for example, by failing to account for women’s distinct vulnerabilities or insecure land rights. The article concludes with three practical measures to ensure that women are present at decision-making, and gender responsive planning is institutionalized, and climate policies reflect the experiences of all citizens. But the argument is now stronger for why it would be good governance to admit women’s voices in climate governance: not just because it is a matter of social justice, but because it can also translate into fairer and more robust low-carbon development.